STRATEGI MEMBANGUN BRAND IMAGE DALAM MENINGKATKAN DAYA SAING LEMBAGA PENDIDIKAN - Wahyu Zakaria; Ulfa Yuniati; Euis Evi Puspitasari (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
Brand Image is a compilation of assumptions in the minds of consumers regarding a brand. Building a brand image in a good educational institution has a competitive influence. Brand Image in an educational institution is one of the important steps in fulfilling the maximum reputation in the minds of the wider community.The research objectives are: 1) To find out the efforts made by the strategy to form a brand image in increasing the competitiveness of educational institutions at Tanjungsari State Agricultural Development Vocational School; 2) To find out how to maintain the existence of the brand image of agricultural education institutions; 3) To find out what are the supporters and obstacles to building a brand image in increasing the competitiveness of educational institutions at Tanjungsari State Agricultural Development Vocational School. This research uses a qualitative approach with a case study research design. This research uses data collection methods, namely Field Observations and Intensive-depth Interview. The technique of analyzing data is data reduction, data presentation, and data verification. To check the validity of the data, triangulation of sources is carried out and discussions with supervisors and colleagues are carried out. The results of the study focused on SMK PPN Tanjungsari in a strategy to build a brand image to increase the competitiveness of educational institutions in surgery with the theory of brand identity, brand personality, brand association , brand attitude & behavior, and brand benefit & competence. Keywords: brand image, competitiveness, educational institutions, strategy